2020
DOI: 10.1145/3403954
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Technology for Cloud Storage

Abstract: The demand for Blockchain innovation and the significance of its application has inspired ever-progressing exploration in various scientific and practical areas. Even though it is still in the initial testing stage, the blockchain is being viewed as a progressive solution to address present-day technology concerns, such as decentralization, identity, trust, character, ownership of data, and information-driven choices. Simultaneously, the world is facing an increase in the diversity and quantity of digital info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(39 citation statements)
references
References 71 publications
0
38
0
1
Order By: Relevance
“…Akbar et al [42] elaborated that SLR methodology is based on facts adopted to answer particular research questions from existing literature systematically. SLR considered a major research area in key research methodologies [43]. An advantageous feature of SLR is the reduction of biasness anomalies as compare to traditional result extraction approaches [44].…”
Section: A Systematic Literature Review (Slr)mentioning
confidence: 99%
“…Akbar et al [42] elaborated that SLR methodology is based on facts adopted to answer particular research questions from existing literature systematically. SLR considered a major research area in key research methodologies [43]. An advantageous feature of SLR is the reduction of biasness anomalies as compare to traditional result extraction approaches [44].…”
Section: A Systematic Literature Review (Slr)mentioning
confidence: 99%
“…A comprehensive understanding of the enzymes and genes related to the biosynthesis of intracellular polysaccharides of P. xylostella is helpful to construct high-yield P. xylostella species, to realize the large-scale production of intracellular polysaccharides of P. xylostella , to meet the growing demand of consumers for food and medical treatment. In recent years, a number of studies have shown that the intracellular polysaccharides of cladosporus cladosporus have antioxidant, antibacterial, and anti-inflammatory, antivirus, antitumor, and immunomodulatory functions [ 18 ]. Therefore, the intracellular polysaccharides of Cladosporus cladosporus are gradually developed and applied in food, medicine, and other fields, which has a good development prospect [ 19 ].…”
Section: Porus Xylostensis and Drug Packaging Image Technologymentioning
confidence: 99%
“…In order to solve the storage problem, cloud computing and cloud storage technologies are used in literature [ 7 ] to provide applications. As mentioned in literature [ 8 ], the traditional security problems still exist in cloud computing environment, and even traditional security mechanisms are no longer applicable to applications and data in cloud. In literature [ 9 ], the dual-chain structure of blockchain is proposed, which uses a chained data structure to store blockchain transaction hashes.…”
Section: Introductionmentioning
confidence: 99%